2021
DOI: 10.3390/ijerph18168567
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Review on the Influence of COVID-19 Lockdown and Quarantine Measures on Modifiable Cardiovascular Risk Factors in the General Population

Abstract: Preceding coronavirus outbreaks resulted in social isolation, which in turn is associated with cardiovascular consequences. Whether the current COVID-19 pandemic negatively impacts cardiovascular health is unclear. The aim of the rapid review was to investigate, whether COVID-19 lockdown influences modifiable cardiovascular risk factors (i.e., physical inactivity, sedentary behaviour, smoking, alcohol use, unhealthy diet, obesity, bad blood lipids, and hypertension) in the general population. Medline and EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 105 publications
(299 reference statements)
2
55
0
Order By: Relevance
“…Those in the deteriorating mental health group were more likely to be women, younger, without a partner, and have a previous mental illness [ 33 ]. The review of Freiberg et al [ 30 ] reported, in turn, that physical activity decreased whereas sedentary behavior and alcohol consumption increased during the COVD-19 lockdown. But even though only studies using probability sampling were included in the review there were methodological shortcomings in many of these studies [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Those in the deteriorating mental health group were more likely to be women, younger, without a partner, and have a previous mental illness [ 33 ]. The review of Freiberg et al [ 30 ] reported, in turn, that physical activity decreased whereas sedentary behavior and alcohol consumption increased during the COVD-19 lockdown. But even though only studies using probability sampling were included in the review there were methodological shortcomings in many of these studies [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The review of Freiberg et al [ 30 ] reported, in turn, that physical activity decreased whereas sedentary behavior and alcohol consumption increased during the COVD-19 lockdown. But even though only studies using probability sampling were included in the review there were methodological shortcomings in many of these studies [ 30 ]. The only direct consequence of the pandemic in the present study seems to have been a rise in the proportion who worry about losing their job.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To curb the pandemic, several regional and national governments responded by encouraging people to stay at home and keep distance from each other. Due to these restrictive measures many health behaviors may have changed, among which physical activity levels [1].…”
Section: Introductionmentioning
confidence: 99%